Comparison of Glycated Albumin and Glycated Hemoglobin levels in the management of type 2 diabetic patients in the Tema Metropolis of Ghana. - Bortie, Patience Naa Adaku (2017)
A thesis submitted in fulfillment of the requirements for the degree of Master of Philosophy (Chemical Pathology) In the Department of Molecular Medicine, School of Medical Sciences College of Health,